answersLogoWhite

0


Best Answer
Copy

Square root 2 is the square root of 4 3 is the square root of 9 and so on

User Avatar

Wiki User

โˆ™ 2008-10-07 16:46:51
This answer is:
๐Ÿ™
2
๐Ÿคจ
2
๐Ÿ˜ฎ
3
๐Ÿ˜‚
2
User Avatar

Add your answer:

Earn +5 pts
Q: What is the meaning of Sqrt?
Write your answer...
Submit

Related Questions

What is the simplified expression for radical 192?

192 = 64 * 3, with sqrt() meaning sqare root of (what's in parentheses)So sqrt(192) = sqrt(64) * sqrt(3) = 8 * sqrt(3) [written eight radical three]


Is the square root of 38 rational or irrational?

\sqrt{38}\sqrt{38}\sqrt{38}\sqrt{38}\sqrt{38}\sqrt{38}\sqrt{38}\sqrt{38}\sqrt{38}\sqrt{38}\sqrt{38}\sqrt{38}\sqrt{38}\sqrt{38}\sqrt{38}\sqrt{38}\sqrt{38}\sqrt{38}\sqrt{38}\sqrt{38}\sqrt{38}\sqrt{38}\sqrt{38}\sqrt{38}\sqrt{38}\sqrt{38}\sqrt{38}\sqrt{38}\sqrt{38}\sqrt{38}\sqrt{38}\sqrt{38}\sqrt{38}\sqrt{38}\sqrt{38}\sqrt{38}\sqrt{38}\sqrt{38}\sqrt{38}\sqrt{38}\sqrt{38}\sqrt{38}\sqrt{38}\sqrt{38}\sqrt{38}\sqrt{38}\sqrt{38}\sqrt{38}\sqrt{38}\sqrt{38}\sqrt{38}\sqrt{38}\sqrt{38}\sqrt{38}\sqrt{38}\sqrt{38}\sqrt{38}\sqrt{38}


What is the square root of a squared plus a squared equal?

sqrt(a2 + a2) = sqrt(2a2) = sqrt(2)*sqrt(a2) = sqrt(2)*asqrt(a2 + a2) = sqrt(2a2) = sqrt(2)*sqrt(a2) = sqrt(2)*asqrt(a2 + a2) = sqrt(2a2) = sqrt(2)*sqrt(a2) = sqrt(2)*asqrt(a2 + a2) = sqrt(2a2) = sqrt(2)*sqrt(a2) = sqrt(2)*a


What is the square root of 72 using radicals?

sqrt(72) = sqrt(36*2) = sqrt(36)*sqrt(2) = 6*sqrt(2).sqrt(72) = sqrt(36*2) = sqrt(36)*sqrt(2) = 6*sqrt(2).sqrt(72) = sqrt(36*2) = sqrt(36)*sqrt(2) = 6*sqrt(2).sqrt(72) = sqrt(36*2) = sqrt(36)*sqrt(2) = 6*sqrt(2).


What are the first 16 equations for the wheel of theodorus?

sqrt(1^2 + 1^2 ) = sqrt(2)sqrt(sqrt(2)^2 + 1^2 ) = sqrt(3)sqrt(sqrt(3)^2 + 1^2 ) = sqrt(4)sqrt(sqrt(4)^2 + 1^2 ) = sqrt(5)sqrt(sqrt(5)^2 + 1^2 ) = sqrt(6)sqrt(sqrt(6)^2 + 1^2 ) = sqrt(7)sqrt(sqrt(7)^2 + 1^2 ) = sqrt(8)sqrt(sqrt(8)^2 + 1^2 ) = sqrt(9)sqrt(sqrt(9)^2 + 1^2 ) = sqrt(10)sqrt(sqrt(10)^2 + 1^2 ) = sqrt(11)sqrt(sqrt(11)^2 + 1^2 ) = sqrt(12)sqrt(sqrt(12)^2 + 1^2 ) = sqrt(13)sqrt(sqrt(13)^2 + 1^2 ) = sqrt(14)sqrt(sqrt(14)^2 + 1^2 ) = sqrt(15)sqrt(sqrt(15)^2 + 1^2 ) = sqrt(16)sqrt(sqrt(16)^2 + 1^2 ) = sqrt(17)


What is the simplest square radical form for 50 and 3 square root of 8?

sqrt(50) = sqrt(25*2) = sqrt(25)*sqrt(2) = 5*sqrt(2)3*sqrt(8) = 3*sqrt(4*2) = 3*sqrt(4)*sqrt(2) = 3*2*sqrt(2) = 6*sqrt(2).sqrt(50) = sqrt(25*2) = sqrt(25)*sqrt(2) = 5*sqrt(2)3*sqrt(8) = 3*sqrt(4*2) = 3*sqrt(4)*sqrt(2) = 3*2*sqrt(2) = 6*sqrt(2).sqrt(50) = sqrt(25*2) = sqrt(25)*sqrt(2) = 5*sqrt(2)3*sqrt(8) = 3*sqrt(4*2) = 3*sqrt(4)*sqrt(2) = 3*2*sqrt(2) = 6*sqrt(2).sqrt(50) = sqrt(25*2) = sqrt(25)*sqrt(2) = 5*sqrt(2)3*sqrt(8) = 3*sqrt(4*2) = 3*sqrt(4)*sqrt(2) = 3*2*sqrt(2) = 6*sqrt(2).


What is the square root of A squared B plus the square root of A B squared divided by the square root of AB?

The question is ambiguous because it could refer to [sqrt(A2B) + sqrt(AB2)]/sqrt(AB) = [A*sqrt(B) + B*sqrt(A)]/[sqrt(A)*sqrt(B)] = A/sqrt(A) + B/sqrt(B) = sqrt(A) + sqrt(B) or sqrt(A2B) + sqrt(AB2)/sqrt(AB) = A*sqrt(B) + B*sqrt(A)/[sqrt(A)*sqrt(B)] = A*sqrt(B) + B/sqrt(B) = A*sqrt(B) + sqrt(B) = sqrt(B)*(1 + A)


What is 12 root 6 minus 12 root 12?

12 sqrt(6)-12sqrt(12) = 12 [sqrt(6)-sqrt(12)] sqrt(6)=sqrt(2x3) = sqrt(2) x sqrt(3) sqrt(12)=sqrt(22x3) = sqrt(22) x sqrt(3) = 2 sqrt(3) sqrt(6) - sqrt(12) = sqrt(2) x sqrt(3) - 2 sqrt(3) = sqrt(3) [sqrt(2)-2] So 12 sqrt(6)-12sqrt(12) = 12 sqrt(3) [sqrt(2)-2]


What is the square root of 80 over 45?

sqrt(80/45) = sqrt(16/9) = sqrt(16)/sqrt(9) = 4/3 sqrt(80/45) = sqrt(16/9) = sqrt(16)/sqrt(9) = 4/3 sqrt(80/45) = sqrt(16/9) = sqrt(16)/sqrt(9) = 4/3 sqrt(80/45) = sqrt(16/9) = sqrt(16)/sqrt(9) = 4/3


What is the square root of 12 times 2 square root 18 Times Square root 24?

sqrt(12)*2*sqrt(18)*sqrt(24) = sqrt(4*3)*2*sqrt(2*9)*sqrt(4*2*3) = sqrt(4)*sqrt(3)*2*sqrt(2)*sqrt(9)*sqrt(4)*sqrt(2)*sqrt(3) = 2*sqrt(3)*2*sqrt(2)*3*2*sqrt(2)*sqrt(3) = 24*sqrt(2)*sqrt(2)*sqrt(3)*sqrt(3) = 24*2*3 = 144


Square root of 5 plus square root of 45?

sqrt(5) + sqrt(45) = sqrt(5) + sqrt(9*5) = sqrt(5) + sqrt(9)*sqrt(5) = sqrt(5) + 3*sqrt(5) = 4*sqrt(5)


What is radical 50 added to radical 8?

58


What are the quartic roots of zero plus 16i?

2*sqrt(0.5 + 0.25*sqrt(2)) + 2i*sqrt(0.5 - 0.25*sqrt(2)) -2*sqrt(0.5 - 0.25*sqrt(2)) + 2i*sqrt(0.5 + 0.25*sqrt(2)) -2*sqrt(0.5 + 0.25*sqrt(2)) - 2i*sqrt(0.5 - 0.25*sqrt(2)) 2*sqrt(0.5 - 0.25*sqrt(2)) - 2i*sqrt(0.5 + 0.25*sqrt(2))


Is a square root commutative?

Yes, it is. sqrt(a+b)=sqrt(b+a) sqrt(a) times sqrt(b) = sqrt(b) times sqrt(a)


What is the simplified form of sqrt 300n11?

sqrt(300n11) = sqrt(100n10*3n) = sqrt(100n10)*Sqrt(3n) = 10n5*sqrt(3n)


What is the sqrt of 28 divided by the sqrt 7?

4


What are the 8 eights roots of 256?

2 -2 i*2 -i*2 sqrt(2) + i*sqrt(2) sqrt(2) - i*sqrt(2) sqrt(2) + i*sqrt(2) -sqrt(2) - i*sqrt(2)


Sqrt bracket 10 plus sqrt 51 bracket?

Sqrt (10 + sqrt 51) = sqrt (10 + 7.14) = sqrt 17.14 = 4.14


Sqrt 24x 4th divided by sqrt 3x equals?

sqrt(24x4) / sqrt(3x) = sqrt(24x4/3x) = sqrt(8x3) = sqrt(2x times 4x2) = 2x sqrt(2x) or (2x)1.5


What is 2 x the square root of 12 plus the square root of 27?

2*sqrt(12) + sqrt(27) = 2*sqrt(4*3) +sqrt(9*3) = 2*sqrt(4)*sqrt(3) + sqrt(9)*sqrt(3) = 2*2*sqrt(3) + 3*sqrt(3) = 4*sqrt(3) + 3*sqrt(3) = 7*sqrt(3)


What is radical 12 times radical 20?

sqrt(12)*sqrt(20) = sqrt(12*20) = sqrt(240) = sqrt(16*15) = sqrt(16)*sqrt(15) = 4*sqrt(15)


How do you divide 28 by the square root of 8?

28/sqrt(8) multiply top and bottom by sqrt(8) = 28*sqrt(8)/[sqrt(8)*sqrt(8)] = 28*sqrt(8)/8 = 7*sqrt(8)/2 But sqrt(8) = sqrt(4*2)= sqrt(4)*sqrt(2) = ±2*sqrt(2) then 7*sqrt(8)/2 = ±7*2*sqrt(2)/2 = ±7*sqrt(2)


What is 14 radical 20 minus 3 radical 125?

14*sqrt(20) - 3*sqrt(125) = 14*sqrt(4*5) - 3*sqrt(25*5) = 14*sqrt(4)*sqrt(5) - 3*sqrt(25)*sqrt(5) = 14*2*sqrt(5) - 3*5*sqrt(5) = 28*sqrt(5) - 15*sqrt(5) = 13*sqrt(5)


How do you multiply square roots?

SQRT(x) * SQRT(y) = SQRT(x*y) Example: SQRT(3) * SQRT(27) = SQRT(81) = 9


Simplify these surds 2 rt 27 - rt 3?

2*sqrt(27) - sqrt(3) = 2*sqrt(9*3) - sqrt(3) = 2*sqrt(9)*sqrt(3) - sqrt(3) = 2*3*sqrt(3) - sqrt(3) - 6*sqrt(3) - srt(3) = 5*sqrt(3)